Modelagem e simulação do processo de esterilização térmica em batelada de vegetais em conserva - Fravet, Fanny Ferreira Melo Fávero de (2006)
The thermal food sterilization is based on the application of temperature conditions for established periods that perform a commercial sterilization of microorganisms, spores and enzymes that has as main goal the attainment of safe products for consumption during extended periods of time. This work addresses the sterilization processing of canned food for the action of heat and introduces a novel mathematical model capable of describing the heat transfer during the thermal treatment of canned vegetables, simulating a processing in a retort. The adopted retort works with vapor, it is horizontal with multiples stages during a batch sterilization cycle. With a modeling methodology, representative partial models of the thermal exchange in the grain/vegetable and can were developed, with posterior coupling of these models in a retort unit model. The considered dynamic models possess 1D level of detail for vegetables, 2D level of detail for the can. The used numerical methods for the solution of the coupled set of partial and ordinary differential equations were the orthogonal collocation technique coupled to the method of lines (MOL). The model was validated through a comparison of the results with values based on thermal penetration curve during peas sterilization reported in the literature. The results for this study show that the proposed model satisfactorily represents the process of canned food sterilization. It also indicates that the lethality could be defined as the monitoring function for online process control, leading to suitable and safe methods for safe production of a sterilized canned product.